Advances in the Development of Anti-Haemonchus contortus Vaccines: Challenges, Opportunities, and Perspectives - Muhammad Ehsan; Rui-Si Hu; Qin-Li Liang; Jun-Ling Hou; Xiaokai Song; Ruofeng Yan; Xing-Quan Zhu; Xiangrui Li (Vaccines, 2020)
The gastrointestinal nematode parasite Haemonchus contortus (H. contortus) is a resident of tropical and subtropical regions worldwide that imposes significant production losses, economic losses, and animal health issues in the small ruminant industry, particularly sheep and goats. Considerable efforts have been made to understand how immunity is elicited against H. contortus infection. Various potential vaccine antigens have been tested by different methods and strategies applied in animal models, and significant progress has been made in the development of vaccines against H. contortus. This review highlighted and shared the knowledge about the current understanding of host immune responses to H. contortus and ongoing challenges in the development of a protective, effective, and long-lasting vaccine against H. contortus infection. We have also pinpointed some achievements and failures in the development and testing of vaccines, which will establish a road map for future research directions to explore new effective vaccine candidates for controlling and preventing H. contortus infection.